Investigating human impacts on rocky reefs using measures of complexity and relief from 3D photogrammetry - Jessica Wright; Jon Chamberlain (Ecosphere, 2024)
Abstract The structural complexity of a habitat is linked with the health and biodiversity of the ecosystem. Computational methods analyzing 3D representations of the environment allow for accurate measurement; however, rocky reef environments that feature gullies, arches, stacks, and ledges may be inaccurately represented using standard measures of complexity. This article presents a novel assessment of structural complexity through relief calculated from 3D reconstructions of marine environments, tailored for rocky reefs with vertical features. This method is tested in two case studies: a tropical coral reef in Indonesia and a rocky (chalk) reef in the United Kingdom. Chalk reef relief was not correlated with vector dispersion or fractal dimension and was weakly correlated with rugosity (r=0.3781); however, in two comparison tropical reef datasets, relief correlated moderately with vector dispersion on both coral reefs (r=0.4657,r=0.4934) and moderately‐strongly with rugosity (r=0.4023,r=0.6703). On the chalk reef, tailored complexity metrics confirmed the previous finding that catch‐size Cancer pagurus abundance (≥115 mm) was correlated with fractal dimension (r=0.4499), indicating that adults preferred elevated, complex reefs. Analysis showed correlations between relief and low‐severity chalk damage (r=0.3931) and between relief and abrasion damage (r=0.4109), whereas previous research had indicated that damage was not correlated with complexity (assessed computationally with rugosity, fractal dimension, and vector dispersion). Surveying marine environments with multicamera arrays and 3D photogrammetry can drastically reduce the time and cost of fieldwork surveys and provide accurate measures of complexity across survey sites. Adapting complexity metrics to habitat‐specific topography provides valuable insight (in this case, into rocky reef marine habitats). Findings from the UK case study support the continued monitoring of the Cromer Shoal Chalk Bed Marine Conservation Zone (MCZ).